2018
DOI: 10.1080/17482631.2018.1490623
|View full text |Cite
|
Sign up to set email alerts
|

Providing healthy diets for young children: the experience of parents in a UK inner city

Abstract: Objectives: There is a consistent body of evidence to demonstrate that obesity in very early childhood tends to continue into adolescence and through to adulthood. Parental practices in relation to food can have an effect on this trajectory, however existing studies reporting on interventions for treating obesity suggest there is a need to involve populations from demographically diverse backgrounds childhood obesity research. Design/Methods: A qualitative study was carried out using semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
2
16
0
1
Order By: Relevance
“…These findings are consistent with previous research addressing parent perception of the snacking environment in youth sports (Gray et al, 2015;Rafferty et al, 2018). Results from this study were also similar to findings from other research citing barriers parents encounter in providing healthier foods for children, such as time, cost, adherence to perceived social norms, avoidance of conflict between parents and children, and children's preferences for foods high in sugar, salt, and fat (Goldthorpe, Ali, & Calam, 2018;Haroldson, Cordell, & Haldeman, 2015;Nepper & Chai, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous research addressing parent perception of the snacking environment in youth sports (Gray et al, 2015;Rafferty et al, 2018). Results from this study were also similar to findings from other research citing barriers parents encounter in providing healthier foods for children, such as time, cost, adherence to perceived social norms, avoidance of conflict between parents and children, and children's preferences for foods high in sugar, salt, and fat (Goldthorpe, Ali, & Calam, 2018;Haroldson, Cordell, & Haldeman, 2015;Nepper & Chai, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Children’s food preferences, particularly the refusal of fruit and vegetables in favour of more ‘palatable’ and unhealthier options, was a notable barrier discussed across all of the focus groups, a finding that has been identified across other migrated populations globally [ 14 , 59 , 60 , 61 ]. Children have been shown to have a genetic predisposition and evolutionary derived preference for sweet foods and a dislike of bitter foods [ 62 ], which can vary by age.…”
Section: Discussionmentioning
confidence: 96%
“…In our results, some parents and commenters held the view that the child's personality might be the reason behind obesity and consequently, the parents are incapable of solving the situation. Another study found similar results: mothers felt that one reason why they were not able to provide healthy food for the child was because the child had special needs or food preferences [52].…”
Section: Discussionmentioning
confidence: 81%
“…Offering advice on lifestyle changes is not what parents always need or want. Parents want a sensitive attitude in counselling [19] and parents with a child with special needs want speci c advice [20] .Some parents feel that they already know enough about healthy lifestyles [21], and they might feel that health and happiness are more important than weight [22]. Alternatively, they might acknowledge that their child is overweight, but do not perceive it as a related health risk [23].…”
mentioning
confidence: 99%